cAMP-mediated Induction of Cyclin E Sensitizes Growth-arrested Adipose Stem Cells to DNA Damage–induced Apoptosis - Ugland, Hege (The American Society for Cell Biology, 2008)
The differentiation capacity of mesenchymal stem cells has been extensively studied, but little is known on cell cycle–related events in the proliferation and differentiation phases of these cells. Here, we demonstrate that exposure to cAMP-increasing agents inhibits proliferation of adipose stem cells (ASCs). This antiproliferative effect is associated with both reduced cdk2 activity and pRB phosphorylation. Concomitantly, however, the level of cyclin E markedly increases upon cAMP induction, indicating that cyclin E may have cdk2-independent functions in these cells besides its role as a cdk2 activator. Indeed, we found indications of a cdk2-independent role of cyclin E in DNA damage–induced apoptosis. 8-CPT-cAMP sensitizes ASCs to γ-irradiation–induced apoptosis, an effect abolished by knockdown of cyclin E. Moreover, cAMP induces early activation of ERK, leading to reduced degradation of cyclin E. The cAMP-mediated up-regulation of cyclin E was blocked by knockdown of ERK or by an inhibitor of the ERK kinase MEK. We conclude that cAMP inhibits cdk2 activity and pRB phosphorylation, leading to reduced ASC proliferation. Concomitant with this growth inhibition, however, cyclin E levels are increased in a MEK/ERK-dependent manner. Our results suggest that cyclin E plays an important, cdk2-independent role in genotoxic stress–induced apoptosis in mesenchymal stem cells.